The analysis of reinforced circular and elliptical cutouts under various loading conditions - Houghton, D. S.; Rothwell, A. (College of Aeronautics, 1961)
The effect of reinforced cutouts in a plane sheet under various loading conditions is considered, and a number of experimental results are given for circular and elliptical cutouts with a uniform plate reinforcement, subjected to various systems of biaxial tension and pure shear. These experiments were conducted using a plane loading frame, and the results are compared with the theoretical plane stress solution. For the circular cutout the effect of neglecting the bending stiffness of the reinforcement is considered. Some additional experiments were carried oUt on a 60 in. diameter pressurised cylinder containing an elliptical hole reinforced according •to Mansfield's neutral hole theory. The strains in the sheet in the region of the neutral hole are .compared with the corresponding strains in the uncut sheet. The experimental results obtained generally show a good agreement with the theory.